TRAUMA DAN REHABILITASI: PERAN BIMBINGAN KONSELING ISLAM DALAM MENYEMBUHKAN LUKA JIWA - Nofita Rahmawati, Roro Kurnia (CV. Jendela Gagasan, 2024)
This research aims to explore the role of Islamic educational counseling in the rehabilitation of psychological trauma and effective strategies to address it. The approach used is a qualitative approach with a literature review study type. The data sources include various scholarly works such as journals, books, and other relevant literature. The research findings indicate that the role of Islamic educational counseling in rehabilitating trauma is crucial. This is based on the counseling process that aims to provide emotional support, guidance, and strategies to cope with the traumatic impact. Meanwhile, an effective strategy that can be used is the responsive service strategy because students experiencing psychological trauma or soul wounds must be considered in terms of their diversity and unique characteristics. Responsive service strategies can also help create an environment that supports the rehabilitation process of soul wounds more effectively.